Fighting with love : the legacy of John Lewis [book with audioplayer] - Cline-Ransome, Lesa (VOX Books, 2024)
"In a beautiful prose telling, the story of a groundbreaking civil rights leader, John Lewis. John Lewis left a cotton farm in Alabama to join the fight for civil rights. He was only a teenager. He soon became a leader of a moment that changed a nation. Walking at the side of his mentor, Dr. Martin Luther King, Lewis was led by his belief in peaceful action and voting rights. Today and always his work and legacy will live on"--